Psychometric Testing of the Smoking Cessation Counseling Scale Among Magnet® Hospital Nurses. (April 2018) - Liu, Wen; Johantgen, Meg; Newhouse, Robin
Psychometrics of the Smoking Cessation Counseling Scale, which measures adherence to evidence-based smoking cessation counseling practice, were originally estimated among rural hospital nurses. The purpose of this study was to estimate the scale's reliability, convergent validity, and factor structure among 289 nurses from 27 acute care Magnet® hospitals. The scale demonstrated acceptable estimates for internal consistency (Cronbach's α = .95, 95% CI = [0.94, 0.96]). Convergent validity was supported by the association with comfort in conducting smoking cessation counseling (coefficient = 3.58, 95% CI = [2.80, 4.37]) and shared vision (coefficient = 0.72, 95% CI = [0.02, 1.42]). A four-factor structure (standard care, basic counseling, advanced counseling, and referral to services) was identified. Findings supported the scale's reliability and convergent validity among Magnet® hospital nurses. Further testing is needed to confirm the four-factor structure and accumulate psychometric evidence among different nursing providers and health care settings to expand the use of the instrument.